Operando Raman Micro-Spectroscopy of Polymer Electrolyte Fuel Cells. Issue 4 (16th January 2016) - Kendrick, Ian; Fore, Jennifer; Doan, Jonathan; Loupe, Neili; Vong, Andy; Dimakis, Nicholas; Diem, Max; Smotkin, Eugene S.
Abstract : Operando Raman micro-spectroscopy of the membrane electrode assembly (MEA) of a fully operating hydrogen/oxygen Nafion electrolyte fuel cell is described. Coarse depth profiling of the fuel cell system enabled appropriate positioning of the micro-spectroscopy laser focal point for MEA catalytic layer spectroscopy. An increase in the ionomer state-of-hydration, from oxygen reduction at the cathode, transitions ion exchange sites from the sulfonic acid to the dissociated sulfonate form. Visualization of density functional theory calculated normal mode eigenvector animations enabled assignments of Nafion side-chain vibrational bands in terms of the exchange site local symmetry: C1 and C3V modes correlate to the sulfonic acid and sulfonate forms respectively. The gradual transition of the MEA spectra from C1 to C3V modes, from the fuel cell open circuit voltage to the short circuit current respectively, demonstrate the utility of vibrational group mode assignments in terms of exchange site local symmetry.